COVID-19 and Mental Health in Vulnerable Populations : A Narrative Review - Das, Abhery; Bruckner, Tim; Saxena, Shekhar; Alqunaibet, Ada; Almudarra, Sami; Herbst, Christopher H.; Alsukait, Reem; El-Saharty, Sameh; Algwaizini, Abdullah (World Bank, Washington, DC, 2021)
This paper examines the global implications of COVID-19 on mental health, with a focus on four particularly vulnerable populations: (1) unemployed adults; (2) youth; (3) older-age populations; and (4) healthcare workers. Considering the global public health burden of mental disorders, understanding COVID-19’s psychological impact on vulnerable populations may provide policy makers with the information necessary to effectively direct resources. The paper focuses on these populations because racial, gender, and social class disparities endure in most educational and work opportunities.25 Additionally, health systems and work environments can perpetuate inequality among vulnerable populations, often leading to worse health outcomes. Previous pandemics and natural disasters have exacerbated income and health disparities for vulnerable populations.25 Similarly, the economic shutdown may disproportionately affect low-income or racial minority workers who work in sector most affected by COVID-19. Youth and older populations remain vulnerable because of factors associated with their age, whereas frontline healthcare workers face overwhelmed health systems and a higher risk of infection. Focusing on these vulnerable populations, the narrative review summarizes the literature addressing mental health and the COVID-19 pandemic. This paper is organized as follows: the next section summarizes current literature on the psychological impact of COVID-19 on four vulnerable populations. The following section then summarizes the findings for each of the populations, followed by a section discussing those results. The next sections provide an understanding of the current state of global mental health and recommend short, medium, and long-term policy solutions.